Zagotavljanje ekonomske, pravne in socialne varnosti delavcem v novih oblikah dela ter v netipičnih oblikah zaposlitve - Pogačar, Peter (Podjetje in delo, 2018)
Working environment is nowadays influenced by many factors, among which the most important are: fast developments of new technologies, digitalisation, new ways of work organisation and demographic changes... The article analyses the influence of digitalisation on the future of working environment and workers, as well as the influence of new forms of work from the perspective of legal, economic and social security of the persons performing new forms of work. Digitalisation and new forms of work can definitely result in a positive effect, but the task of policy makers should be on preventing the risks for decent work.
Keywords: delo; digitalizacija; dostojno delo; ekonomska varnost; nove oblike dela; pravna varnost; prihodnost; socialna varnost